Pengelolaan Strategi Pemasaran Lembaga Pendidikan Berbasis Sosial Media di SMKN 1 Sragen - Salsa Widya (Program Studi Manajemen Pendidikan Islam, 2022)
This study aims to describe the description of the management of educational marketing strategies using social media in SMK Negeri 1 Sragen. Social media is considered appropriate and effective to be used as a marketing medium for school education because it is easily accessible to all groups and has great opportunities in building relationships with consumers (students). This study uses qualitative research methods with data collection techniques carried out through interviews, documentation and analysis of social media content. The results show that the previous school's marketing strategy using traditional strategies by distributing pamphlets, brochures, and oral information has now evolved with the times by switching to using social media. The most effective social media used in the education marketing process at SMK Negeri 1 Sragen are 3, namely: instagram, youtube, and website. The supporting factors for the education marketing strategy include a supporting internet network, human resources and complete facilities and the inhibiting factors for the educational marketing strategy include the reach and time for promotion.